Dampak Penggabungan Tiga Bank Syariah di Indonesia - Alif Ulfa (Jurnal Ilmiah Ekonomi Islam, 2021)
Bank Syariah Indonesia (BSI) was born from the merger of 3 state-owned Islamic banks (BUMN), namely PT Bank BRI Syariah Tbk (BRIS), PT Bank BNI Syariah (BNIS), and PT Bank Syariah Mandiri (BSM). BSI is the government's strategy to make Indonesia one of the world's Islamic financial centers. This study focuses on aspects affected by the merger of 3 Islamic banks, such as customers, employees, and the community. This study uses a qualitative method with a library research approach. The data used is secondary data, namely data sourced from existing literature or references. The results of the merger have an impact on several elements such as customers, employees, and the community. a) Customers can still transact using card-based electronic money. Customers only need to do bank migration, b) Employee status from BNI Syariah, BRI Syariah, and Bank Syariah Mandiri remains an employee of Bank Syariah Indonesia and there will be no termination of employment, c) Bank Syariah Indonesia (BSI) educates the public by launching a Sharia Economics literacy program and accelerating the completeness of the halal value chain in the development of the halal industry, financing UMKM supporting it, and participating in financing large-scale projects using sharia schemes.